The The Role of Islamic Financial Institutions in Women's Economic Empowerment - Ayu Karisma; Mohamad Abdun Nasir; Sanurdi Sanurdi (JURNAL PENDIDIKAN IPS, 2025)
Women's economic empowerment still faces various challenges, especially in developing countries and Muslim communities. Islamic financial institutions (IFIs) offer a promising alternative with sharia principles that prohibit usury and emphasize profit-sharing and partnership systems. This study aims to explore the role of IFIs in supporting women's economic empowerment by providing access to sharia-based financing such as murabahah and musyarakah, business training and mentoring, group savings systems, and financial protection products such as takaful. The methodology used is a descriptive qualitative approach with data collection through in-depth interviews and literature studies. Data analysis was conducted to identify the contribution of IFIs to increasing the economic capacity of women, especially micro, small, and medium enterprises (MSMEs). The results of the study indicate that IFIs have significant potential in supporting women's economic independence, which has an impact on improving family welfare and strengthening the economic structure of society. This study also found opportunities for IFIs development through financial product innovation that is responsive to women's needs and the use of technology to expand the reach of services. In conclusion, efforts to empower women's economy through IFIs need to continue to be developed strategically in order to realize inclusive and sustainable economic development.